Pengaruh Pembelajaran IPA dengan Pendekatan Saintifik Menggunakan Media Powerpoint Interaktif Terhadap Kemampuan Berpikir Kritis Siswa Kelas IV - Mahdalena; Irwan Koto; Endang Widi Winarni (Jurnal Kajian Pendidikan Dasar, 2024)
This study aims to analyze the effect of science learning with a scientific approach using interactive PowerPoint media on the critical thinking skills of fourth grade students.This research is a quantitative research. The method used is Quasi Experimental Design (pseudo-experimental research). Quasi Experimental Designaims to determine the differences between two variables or more groups that are the subject of research, because the sample is not randomly selected but has been formed in the form of classes. Therefore, the research sample was divided into two groups, namely the experimental class and the control class. As an experimental class in this study were 20 grade IV students at SDN 2 Sungai Pinang and as a control class were 20 grade IV students at SDN 1 Sungai Pinang. Data collection technique is done by test pretest andposttest. The instrument given was essay questions consisting of 10 questions, consisting of 5 questions on the induction aspect and 5 questions on the deduction aspect. The results of this study indicate that the average value of the induction aspect variable between the experimental class and the control class has an increase difference of 44.00%. While the average value of the deduction aspect variable has an increase difference of 39.40%. So it can be concluded that there is a significant effectscience learning with a scientific approach using interactive powerpoint media.to critical thinking skills of grade IV students.